MODERNISASI SANKSI ADAT DALAM PENYUSUNAN AWIG-AWIG ORGANISASI SEKAA TERUNA - Widnyana, I Made Adi (Institut Hindu Dharma Negeri Denpasar, 2021)
AbstractThe sustainability of balinese indigenous civilization can not be released from the existence of Indigenous Villages and banjar adat as a unity of indigenous peoples guided by customary rules in the form of awig-awig, perarem, or other forms. It also organizes a youth organization in Bali called sekaa teruna which is part of banjar adat. In this era the existence of awig-awig seems like a mere rule crest, because many contents of awig-awig mainly on the sanctions section in ancient times that are no longer relevant to be applied in the present. Therefore, in this paper will be discussed in advance on How the concept of formulation of awig-awig, How the form of old customary sanctions that have been applied in Bali and have been irrelevant applied, and How the modernization process can be done against the irrelevant customary sanctions. From this it is seen that the concept of formulation of awig-awig in Bali is generally related to the concept of Tri Hita Karana, while the old forms of customary sanctions that are considered irrelevant include: customary sanctions against the case of twin buncing, sanctions kesepekang, forced marriage sanctions, and other types of sanctions. Modernization of ancient customary sanctions can be done by youth organizations by incorporating customary sanctions that can be applied by youth in the present, so that the existence of such awig-awig is not only limited as a symbol.Keywords: Awig-awig, Modernization, Customary Sanctions, Sekaa Teruna